A Full-Profile Conjoint Analysis to Identify University Students’ Preferences Toward Food Delivery Services: A Case Study of the Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta - Supandi, Epha Diana; Rochmiyani, Fitri (Journal of Industrial Engineering and Halal Industries, 2025)
The rapid development of digital technology has transformed consumer behavior, particularly in fulfilling food needs through online food delivery services. University students represent one of the most active user groups due to their high mobility and preference for practical lifestyles. This study aims to analyze students’ preferences toward food delivery service attributes and to identify the most influential factors in determining their choices. The research involved 100 respondents from the Faculty of Science and Technology, Universitas Islam Negeri Sunan Kalijaga Yogyakarta, using the traditional conjoint analysis method with a full-profile design approach. Six attributes were examined: type of service, price, payment method, courier service, food quality, and service quality. The results indicate that price has the highest level of importance (25.401%), followed by type of service (22.230%), service quality (16.231%), courier service (15.926%), payment method (10.960%), and food quality (9.252%). The most preferred combination of attributes includes GrabFood or GoFood services with promotional prices, uniformed couriers, diverse food options, and fast delivery. These findings suggest that promotional pricing strategies and service quality improvements are key factors for online food delivery providers to enhance customer satisfaction and attract student users.